2017
DOI: 10.1021/acs.jpca.7b08252
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Excited-State Dynamics of all-trans-Capsanthin in Organic Solvents

Abstract: The C carotenoid capsanthin is of photophysical interest because it belongs to the family of terminally carbonyl-substituted apocarotenes. These have the potential to exhibit intramolecular charge transfer (ICT) character in the excited state. We studied its ultrafast dynamics in different solvents using broadband transient absorption spectroscopy in the 260-1600 nm range. Photoexcitation initially populated the S(1B) state which decayed to the S(2A) state in 120-150 fs. The lifetime of the S state decreased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The recorded transient profiles were shown in Figure a,b and Figure S5 (Supporting Information). A typical oscillatory triple‐peak signal was shown up with a negative peak at 488 nm, which can be assigned to the relaxed carriers at the indirect band edge 32,41. The bleach kinetic at 488 nm was monitored and further analyzed by a single exponential fitting mode, as displayed in Figure 4c.…”
Section: Resultsmentioning
confidence: 99%
“…The recorded transient profiles were shown in Figure a,b and Figure S5 (Supporting Information). A typical oscillatory triple‐peak signal was shown up with a negative peak at 488 nm, which can be assigned to the relaxed carriers at the indirect band edge 32,41. The bleach kinetic at 488 nm was monitored and further analyzed by a single exponential fitting mode, as displayed in Figure 4c.…”
Section: Resultsmentioning
confidence: 99%
“…33) All diffraction reflections could be indexed as a hexagonal (CH 3 NH 3 ) 3 Bi 2 I 9 with space group P6 3 /mmc. 34) The (CH 3 NH 3 ) 3 Bi 2 I 9 layers annealed at 120140 °C were randomly oriented. On the other hand, 002, 004, and 006 diffraction reflections at 7.9, 16.1, and 24.4°, respectively, were observed for the film annealed at 150 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, Miyasaka et al investigated different device structures, e.g., anatase or brookite TiO 2 as the mesoscopic scaffold and planar structure, correspondingly. They found that the physical junction was poorly formed and MA 3 Bi 2 I 9 film was nonuniform on brookite TiO 2 and planar substrates, in accordance with the conclusion made by Lenzer et al that MA 3 Bi 2 I 9 should employed bulk heterojunction architecture to render the efficient carrier separation. Considering its absorbance edge of 620 nm, the highest J sc would be 10 mA cm −2 .…”
Section: Ternary Bismuth Halidesmentioning
confidence: 99%